Strategi dalam Meningkatkan Kedisiplinan Siswa - Arfandi, Arfandi (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2022)
Disciplined life really needs to be trained a2nd accustomed to in everyday life, because with this habit humans will really be trained and can experience a meaningful life, gain the trust of others because of their high sense of discipline and responsibility. The words of discipline are easy to say but quite difficult to implement. The application of discipline both at the educational level and its application in everyday life must be optimized so that students/communities in filling this globalization era can be able to compete in the field in a healthy and fair manner. Therefore, in the development of disciplinary education, it is very necessary to have a good and well-planned disciplinary education strategy. The focus of this research is the strategy for improving student discipline at MTs Salafiyah Al Asy'ariyah Mangaran Situbondo while the purpose of this research is to describe strategies for improving student discipline at MTs Salafiyah Al Asy'ariyah Mangaran Situbondo. This research method uses descriptive qualitative research. Data sources in this study were obtained by researchers from key informants, namely people who can provide information to researchers, data collection techniques consisting of; Interviews. Observation; and Documentation. The findings of the research results are the strategies used by MTs Salafiyah Al Asy'ariyah Mangaran Situbondo in increasing student discipline, namely: a) Preparation of vision, mission, motto and goals, b) Preparation of special activity programs c) Rules of conduct, d) Socialization, e) Approach, f) Facilities and Infrastructure, and g) Evaluation.